2011
DOI: 10.1007/s00431-011-1425-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with parental acceptance and refusal of pandemic influenza A/H1N1 vaccine in Turkey

Abstract: The objective of this study was to investigate the parents' attitudes towards and identify the possible factors associated with pandemic H1N1 vaccine uptake that was recommended to children between 6 months and 5 years of age. A questionnaire exploring the attitudes of parents to H1N1 vaccine was given to parents of children 6 through 60 months of age attending to Akdeniz and Gazi University Hospitals' well-child departments between 15 November 2009 and 15 January 2010. The questionnaire included questions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
6
27
0
Order By: Relevance
“…Their attitudes are also known to be influenced by medical and social factors (18,27). In previous studies, it was shown that people with higher education levels were more likely to immunize their children with the influenza vaccine (18,27). Most of our patients' parents were very sensitive about their children.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Their attitudes are also known to be influenced by medical and social factors (18,27). In previous studies, it was shown that people with higher education levels were more likely to immunize their children with the influenza vaccine (18,27). Most of our patients' parents were very sensitive about their children.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, in the study group of Akis et al, parents were more likely to have older children vaccinated (18). This may either be due to parental perception about younger children being more prone to vaccine side effects or to the belief that it is easier to keep younger children at home.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This was manifested by a spectrum of attitudes, such as: perceiving susceptibility to swine flu as low, believing that the epidemic was not serious, believing the swine flu was a mild disease. 74,[83][84][85]89,92,93,95,96,98,100 These motives became very apparent in studies conducted at later time points, but was observed also in earlier surveys as well.…”
Section: Acceptance Of the A/h1n1 Vaccine: When Anticipation And Realmentioning
confidence: 85%